Цифровий контроль та аудит у сфері публічних фінансів - Качула, Світлана Валентинівна; Kachula, Svitlana (Чорноморський національний університет імені Петра Могили, 2025)
У статті розглянуто сучасні підходи до цифрового контролю та аудиту у сфері публічних фінансів, з впровадженням інноваційних технологій, таких як штучний інтелект, блокчейн, великі дані та машинне навчання. Проаналізовано основні виклики, що перешкоджають ефективній цифровій трансформації та обґрунтовано, з метою удосконалення цифрового контролю та аудиту публічних фінансів, необхідність застосування комплексного підходу, який включатиме оновлення законодавства, модернізацію інфраструктури та розвиток кадрового потенціалу. Визначено, що формування інтегрованих інформаційних платформ та культури цифрової відкритості сприятимуть підвищенню прозорості та підзвітності публічних фінансів, так як успішна цифрова трансформація в контролі та аудиті публічнних фінансів вимагає скоординованих зусиль у технологічній, правовій та освітній сферах, закладаючи основу для сталого розвитку та стійкості систем управління публічними фінансами в умовах постійно мінливих викликів. This article explores the critical role of digital control and auditing in enhancing the efficiency, transparency, and accountability of public finance management. It focuses on the adoption of innovative technologies, including artificial intelligence, blockchain, big data analytics, and machine learning, which are revolutionizing traditional auditing methods and enabling more accurate and timely detection of financial irregularities. The study identifies significant challenges to effective digital transformation, such as outdated regulatory frameworks that do not fully address digital evidence admissibility and data privacy concerns, technological disparities across public institutions, and a lack of sufficient digital competencies among auditors. Emphasizing the necessity of a holistic and multi-dimensional approach, the article argues for comprehensive legislative reforms, modernization of technical infrastructure, and ongoing professional development programs to equip auditors with the necessary skills for the digital era. The research also highlights the importance of developing integrated information platforms that facilitate seamless data interoperability and promote transparency, accountability, and collaboration within public financial oversight. Drawing on international best practices and case studies, the article illustrates how coordinated efforts among government bodies, private sector stakeholders, and civil society can drive sustainable digital transformation in public finance auditing. Ultimately, the findings underscore that successful implementation of digital control mechanisms requires not only technological advancements but also profound institutional and cultural changes aimed at fostering openness, trust, and responsiveness. This integrated approach will contribute to more effective, transparent, and accountable management of public resources in the context of rapidly evolving technological and socio-economic challenges, thus ensuring greater resilience and sustainability of public financial systems.
Digital control and audit in public finance
Keywords: публічні фінанси; public finances; фінансовий контроль; financial control; державний аудит; state audit; цифровий аудит; digital audit; бюджетна прозорість; budget transparency; ризик-орієнтований підхід; risk-based approach; цифрові технології; digital technologies; автоматизовані системи контролю; automated control systems